1. Преобразуй в многочлен
1) ![(y-4)^{2}=(y-4)(y-4)=y^{2}-4y-4y+16=y^{2}+(-4y-4y)+16=y^{2}-8y+16 (y-4)^{2}=(y-4)(y-4)=y^{2}-4y-4y+16=y^{2}+(-4y-4y)+16=y^{2}-8y+16](https://tex.z-dn.net/?f=%28y-4%29%5E%7B2%7D%3D%28y-4%29%28y-4%29%3Dy%5E%7B2%7D-4y-4y%2B16%3Dy%5E%7B2%7D%2B%28-4y-4y%29%2B16%3Dy%5E%7B2%7D-8y%2B16+)
=================================================================
2) ![(7x+a)^{2}=(7x+a)(7x+a)=49x^{2}+(7ax+7ax)+a^{2}=49x^{2}+14ax+a^{2} (7x+a)^{2}=(7x+a)(7x+a)=49x^{2}+(7ax+7ax)+a^{2}=49x^{2}+14ax+a^{2}](https://tex.z-dn.net/?f=%287x%2Ba%29%5E%7B2%7D%3D%287x%2Ba%29%287x%2Ba%29%3D49x%5E%7B2%7D%2B%287ax%2B7ax%29%2Ba%5E%7B2%7D%3D49x%5E%7B2%7D%2B14ax%2Ba%5E%7B2%7D)
=================================================================
3) ![(5c-1)(5c+1)=25c^{2}+(5c-5c)-1=25c^{2}-1 (5c-1)(5c+1)=25c^{2}+(5c-5c)-1=25c^{2}-1](https://tex.z-dn.net/?f=%285c-1%29%285c%2B1%29%3D25c%5E%7B2%7D%2B%285c-5c%29-1%3D25c%5E%7B2%7D-1+)
=================================================================
4) ![(3a+2b)(3a-2b)=9a^{2}-6ab+6ab-4b^{2}=9a^{2}+(-6ab+6ab)-4b^{2}=9a^{2}-4b^{2} (3a+2b)(3a-2b)=9a^{2}-6ab+6ab-4b^{2}=9a^{2}+(-6ab+6ab)-4b^{2}=9a^{2}-4b^{2}](https://tex.z-dn.net/?f=%283a%2B2b%29%283a-2b%29%3D9a%5E%7B2%7D-6ab%2B6ab-4b%5E%7B2%7D%3D9a%5E%7B2%7D%2B%28-6ab%2B6ab%29-4b%5E%7B2%7D%3D9a%5E%7B2%7D-4b%5E%7B2%7D+)
=================================================================
2. Упрости выражение
![(a-9)^{2}-(81+2a)=a^{2}-18a+81-81-2a=a^{2}+(-18a-2a)+(81-81)=a^{2}-20a=a(a-20) (a-9)^{2}-(81+2a)=a^{2}-18a+81-81-2a=a^{2}+(-18a-2a)+(81-81)=a^{2}-20a=a(a-20)](https://tex.z-dn.net/?f=%28a-9%29%5E%7B2%7D-%2881%2B2a%29%3Da%5E%7B2%7D-18a%2B81-81-2a%3Da%5E%7B2%7D%2B%28-18a-2a%29%2B%2881-81%29%3Da%5E%7B2%7D-20a%3Da%28a-20%29)
=================================================================
3. Решите уровнение
![(2-x)^{2}-x(x+1,5)=4 (2-x)^{2}-x(x+1,5)=4](https://tex.z-dn.net/?f=%282-x%29%5E%7B2%7D-x%28x%2B1%2C5%29%3D4)
![4-4x+x^{2}-x^{2}-1,5x=4 4-4x+x^{2}-x^{2}-1,5x=4](https://tex.z-dn.net/?f=4-4x%2Bx%5E%7B2%7D-x%5E%7B2%7D-1%2C5x%3D4)
![4-4x+x^{2}-x^{2}-1,5x-4=0 4-4x+x^{2}-x^{2}-1,5x-4=0](https://tex.z-dn.net/?f=4-4x%2Bx%5E%7B2%7D-x%5E%7B2%7D-1%2C5x-4%3D0)
![(x^{2}-x^{2})+(-4x-1,5x)+(4-4)=0 (x^{2}-x^{2})+(-4x-1,5x)+(4-4)=0](https://tex.z-dn.net/?f=%28x%5E%7B2%7D-x%5E%7B2%7D%29%2B%28-4x-1%2C5x%29%2B%284-4%29%3D0)
![-5,5x=0 -5,5x=0](https://tex.z-dn.net/?f=-5%2C5x%3D0)
![x=0 x=0](https://tex.z-dn.net/?f=x%3D0)
==================================================================
4. Разложите на множители
1) ![x^{2}-49=(x-7)(x+7) x^{2}-49=(x-7)(x+7)](https://tex.z-dn.net/?f=x%5E%7B2%7D-49%3D%28x-7%29%28x%2B7%29)
==================================================================
2)